Conceptualising the Continuity of Legal Systems and Cultures: International Workshop on “Legal Survivals in Central and Eastern Europe: Socio-Legal Perspectives on Public And Private Law” (Riga Graduate School of Law, Riga, 15–16 June 2024) - Piotr Eckhardt; Rafał Rafał (Acta Universitatis Lodziensis Folia Iuridica, 2025)
The paper describes the debates which took place during the International Workshop on “Legal Survivals in Central and Eastern Europe: Socio-Legal Perspectives on Public and Private Law” (Riga, 15–16 June 2024). The aim of the workshop was to share case studies of legal institutions that have survived despite a socio-economic and political transformation. In the context of Central and Eastern Europe, two transformations in each of the countries in the 20th century are most significant, namely the transition from (authoritarian) capitalism to state communism in the 1940s and the transition back from state communism to capitalism, but this time coupled with democracy and rule of law at the turn of the 1980s and the 1990s. There is certainly a need to analyse legal survivals in the context of Central and Eastern Europe and its transformations which have generally favoured a discontinuity of legal culture, therefore making any continuity in a sense paradoxical and in need of explanation.